Pengaruh Permainan Edukatif dalam Meningkatkan Sikap Sosial pada Siswa SDN Ibun 2 - Nurani Dewi Safitri; Anggi Setia Lengkana; Tedi Supriyadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to determine the effect of educational games on improving social attitudes of elementary school students. The method used was a quantitative approach with a pre-experimental pretest-posttest design, and the sampling technique employed was purposive sampling with criteria of upper-grade students. The treatment was carried out through various educational games, such as jumping game, numeric, quiz, puzzle arrangement, cup pyramid, coordination bridge, roll the ball, and stacko uno. The results showed that the pretest and posttest data were not normally distributed; therefore, further analysis was conducted using the non-parametric Wilcoxon Signed-Rank Test. The findings indicated a significant difference between pretest and posttest scores, which reflects an improvement in students' social attitudes after the treatment. In conclusion, educational games have a significant effect on improving the social attitudes of elementary school students. Keywords: Educational Games, Social Attitudes, Educational Game Skills